Tingkat Serangan Larva Spodoptera frugiperda (Lepidoptera: Noctuidae) pada Tanaman Jagung di Ketinggian Tempat yang Berbeda - Ella Apriyana; Helmi Syaputra; Khairi Sardilla; Nur Amalia N; Tezzia Nofetra; Tika Rahmawati; Chandra Irsan (Seminar Nasional Lahan Suboptimal, 2021)
Apriyana E, Syaputra H, Sardilla K, Nasution NA, Nofetra T, Rahmawati T, Irsan C. 2021. Tingkat Serangan Larva Spodoptera frugiperda (Lepidoptera: Noctuidae) pada Tanaman Jagung di Ketinggian Tempat yang Berbeda. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 563-569.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Corn (Zea mays L.) is a commodity that is widely cultivated in Indonesia. Cultivation is carried out in various areas, from the lowlands to the highlands. Cultivation of corn plants is inseparable from pest attacks, one of which is Spodoptera frugiperda (Lepidoptera: Noctuidae). The altitude of the place is not known with certainty with the influence of S. frugiperda attack. In terms of knowing the attack rate of S. frugiperda on corn was done by collecting data. Aim to find out how the effect of altitude on the level of attack S. frugiperda. From the results of the literature study showed that at altitude <500 m above sea level to 100% attack. At an altitude of 500-1000 meters above sea level, the attack was categorized as large. Meanwhile, at an altitude of > 1000 masl, the attack was categorized as high with a certain temperature range. The attack rate of S. frugiperda was also known to be influenced by climate and the presence of natural enemies in the ecosystem. So, it can be concluded that altitude didn't absolutely affect the attack of S. frugiperda on maize.